A Connection Between Almost Periodic Functions Defined on Timescales and ? - Lizama-Yanez, C (Taylor and Francis Ltd., 2014)
In this paper, we prove a strong connection between almost periodic functions on timescales and almost periodic functions on (Formula presented.). An application to difference equations on (Formula presented.) is given. © 2014, © 2014 Taylor & Francis.